TESTING & ANALYSIS OF TORQUE LIMITER TIMER BELT SPINDLE DRIVE FOROVERLOAD PROTECTION - Pankaj Thakuji Thorve; Dr. S.B. Zope (International Journal of Innovations in Engineering Research and Technology, 2021)
The presence of cracks causeschanges in the physical properties of a structure which introduces flexibility, and thus reducing the stiffness of the structure with an inherent reduction in modal natural frequencies. Consequently it leads to the change in the dynamic response of the beam. In this paper, A model for free vibration analysis of a beam with an open edge crack has been presented. Variations of natural frequencies due to crack at various locations and with varying crack depths have been studied. A parametric study has been carried out. The cracked beams with different boundary conditions have been analyzed. The results obtained by Euler’s beam theory